Investigating the Application of Artificial Intelligence in the Pediatric Oncology - Mohammad Naderisorki; Maryam Rezapour; Mehdi Naderi Soorki (Mazandaran University of Medical Sciences, 2024)
Since Alan Turing proposed the concept of using computers for intelligent simulation of behavior and critical thinking, artificial intelligence has progressed in various fields. In medicine, artificial intelligence is used in three subfields: Machine learning (ML), deep learning (DL), and computer vision. Considering the increasing use of artificial intelligence in pediatric oncology and cancer treatment, there is a need for studies and research projects specifically focused on pediatric oncology. In oncology, especially childhood malignancies, artificial intelligence can help doctors as a new tool.